Laju Pertumbuhan dan Tingkat Kelangsungan Hidup Transplantasi Karang Acropora secale di Pantai Serangan dan Pantai Geger, Bali - Luh Putu Ayu Depi Nurcahyani; I Wayan Gede Astawa Karang; Widiastuti Widiastuti (Journal of Marine and Aquatic Sciences, 2018)
The status of Indonesian coral reefs are in fair to poor categories, therefore it requires more approaches in order to recover the natural ecosystem. One of the reef restoration method is coral transplantation. Genus Acropora is one of the main constituent of reefs in the Indo-Pacific waters. Reef transplantation may not only rehabilitate the damaged reef, but also an effective way to collect coral for economic purposes. Acropora secale has high economic value as aquarium ornament, however it is vulnerable to the environmental stress and marine pollution. Therefore, finding the suitable transplantation location is one of important part in the transplantation. The objective of this research is to investigate the growth of transplant A. Secale at Serangan and Geger Beach which has different morphology feature. A. secale was Transplanted for 3 months on the 2 x 1 m table with 16 fragments and observed each week. The results obtained are total growth and growth rate of A. secale transplanted on Serangan Beach is significant higher than Geger Beach (P<0.05). The total growth of A. secale on Serangan Beach is higher by 0,83 cm, wider by 0,61 cm, and branches are more 7 branches than Geger Beach. The growth rate of A. secale at Serangan Beach was higher by 0,27 cm/month and wider by 0,21 cm/month than Geger Beach. The survival rate of A. secale on Serangan Beach and Geger Beach is 100% which means that all transplanted corals survive until the end of the study.